Effect of Solid Waste Fly Ash from Vegetable Oil Company in Production of Paving Block - Alexius Luther Ola; Doly Prima Silaban (Jurnal Keramik dan Gelas Indonesia, 2019)
Vegetable oil company produced large amount of fly ash as a solid waste. This waste has to be placed in a special space and this requirement causing problem for the vegetable oil company, such as decreasing of open space and aesthetics value of a place. This study has been aimed to know addition effect of fly ash on paving block quality. This research used variation of fly ash and coarse sand volume, while fine sand and Portland cement volume as a constant value. The result showed that fly ash can be used as filler material of paving block. Sample was analyzed using SNI 03- 0691-1996 procedure and showed highest value of compresisive strength on A1B2 treatment (22.34 Mpa), while the lowest was showed on A3B3 treatment (18.58 MPa). Water absorption values were ranged from 2.41% to 4.48%, and fulfill standart requirement. Based on test result paving block from A1B1, A1B2, A1B3,A2 B1, A2B2 and A2B3 treatment complied quality standart as B grade of paving block (used for parking yard), when A3B2 and A3B3 treatment complied quality standart as C grade of paving block (used for pedestrian base). The best treatment was A1B2 which consisted of (parts) 2 : 8 : 2 of fly ash, sand and Portland cement respectively, with compressive strength value 22.34 MPa and water absorption value 2.60%